The basic definitions of artificial intelligence operating system: "ai-thought” and "ai-emotion” concepts - Kornieiev, S. (Штучний інтелект, 2017)
The article concerns the concept of “Artificial General Intelligence” (AGI) and in particular the issue of basic definitions. The article proposed definitions of the concepts: “AI-Thought” and “AI-Emotion”. These definitions are based on the author’s definitions of "Artificial Intelligence – Individual Type" and “Artificial Intelligence – Collective Type” (“swarm”) were introduced before. The goal of the definitions is to be used in the modelling of AI-OS (Artificial Intelligence Operating System). As seen together the set of formulated definitions allow to model AI-OS for productive use. A distinctive feature of presented definitions is that they, if compared with known ones, allow the simulation and design using known methods and approaches.